2022
DOI: 10.3390/bs12080266
|View full text |Cite
|
Sign up to set email alerts
|

Leading for Innovation: Self-Efficacy and Work Engagement as Sequential Mediation Relating Ethical Leadership and Innovative Work Behavior

Abstract: This research investigated the link between ethical leadership and innovative work behavior by examining the role of self-efficacy as a mediating factor and the sequential mediation of self-efficacy and work engagement. Using a survey approach, data were collected from 441 bank employees in the southern region of Thailand. The findings of the structural equation modeling (SEM) analysis revealed an association between ethical leadership and innovative work behavior and self-efficacy, respectively. Work engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 107 publications
3
8
0
3
Order By: Relevance
“…In addition, Aryee and Chen (2006) conducted similar research in the high-power distance culture of China and observed that psychological factors fully mediated the relation between leader-member exchange and employee outcomes. (2022) and Uppathampracha and Liu (2022).…”
Section: Structural Path Analysismentioning
confidence: 98%
“…In addition, Aryee and Chen (2006) conducted similar research in the high-power distance culture of China and observed that psychological factors fully mediated the relation between leader-member exchange and employee outcomes. (2022) and Uppathampracha and Liu (2022).…”
Section: Structural Path Analysismentioning
confidence: 98%
“…Likewise, research has emphasized sustainable leadership, which helps foster innovation by effectively dealing with environmental challenges (Xuecheng and Iqbal, 2022). Sustainable leadership promotes employees' innovative behavior by inducing employee creative self-efficacy and encouraging participative behaviors (Uppathampracha and Liu, 2022). According to Iqbal et al (2022), a significant positive relationship exists between sustainable leadership and frugal innovation.…”
Section: Literature Review and Hypotheses Development Frugal Innovati...mentioning
confidence: 99%
“…Self efficacy berpengaruh signifikan terhadap perilaku inovatif. Hasil ini didukung oleh penelitian yan dilakukan oleh Uppathampracha & Liu, (2022) dimana pada hasil penelitiannya menunjukkan Self efficacy berpengaruh signifikan terhadap perilaku inovatif karyawan. Pada PT.…”
Section: Pengaruh Self Efficacy Terhadap Perilaku Inovatifunclassified
“…Karyawan yang memiliki persepsi yang kuat terhadap Self efficacy akan memiliki tingkat pencapaian yang lebih tinggi dan tekad yang lebih kuat terhadap tantangan (Bandura. 1994; Uppathampracha & Liu, 2022). Individu yang percaya diri pasti akan memulai sesuatu yang baru dan mengikuti perkembangan dalam jangka Panjang.…”
Section: Pengaruh Self Efficacy Terhadap Perilaku Inovatifunclassified